Reflection of Etymon Proto-Austronesian Bilabial [p] in Nias Language - Andi, Wete Polili (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Historical compositional linguistics or diachronic linguistics is a branch of language science that deals with the kinship relations and line of language. The kinship and historicity of the language is one certain region. The kinship or foundation relationship is abstracted in terms of the term. It is also an implied linguistics fact which is used as the basis of determination and proof of kinship relationship. These linguistics facts illustrate the historical process of the relative languages in the course of time. The tracking and interpretation of the phenomenon on evolution of language in the past is the features of diachronic linguistics.